CODE-SWITCHING AND CODE-MIXING USED BY BOY WILLIAM AND VALENCIA TANOESOEDIBJO IN A VLOG - Fitriyah, Nahda Khoirun (CALL, 2024)
This study investigated the phenomena of code-switching and code-mixing as employed by Boy William and Valencia Tanoesoedibjo, focusing on identifying their types, underlying reasons, and contributing factors. Adopting a qualitative research design, the study analyzed non-numerical data, specifically the spoken utterances of Boy and Valencia in a vlog, where instances of code-switching and code-mixing occur. The classification of code-switching follows the framework proposed by Poplack (1980), while the identification of code-mixing types relies on Hoffman’s (1991) model. Additionally, Hoffman’s (1991) framework is utilized to explore the reasons behind their use of code-switching and code-mixing. To further examine the influencing factors, the study employs the theoretical framework of Bhatia and Ritchie (2004). The findings indicate that Boy and Valencia employed five of the seven identified reasons for code-switching and code-mixing: discussing specific topics, expressing emphasis, using interjections, clarifying speech through repetition, and ensuring clarity for the interlocutor. Regarding the influencing factors, the analysis reveals that participant roles and relationships, situational contexts, message-intrinsic features, and attitudes towards language, including dominance and security, are significant contributors. Moreover, an additional factor identified in the study is their prior experience of living overseas, which further shapes their linguistic choices. Keyword: code-switching, code-mixing, type, reason, factor